Oliguria on the Day of Intubation Is Associated With Mortality in Patients With Acute Respiratory Distress Syndrome. (17th June 2022) - Fadel, Raef A.; Murskyj, Ivanna; Abou Asala, Elian; Nasiri, Nour; Alsaadi, Ayman; Scott, Ashley; Ouellette, Daniel
Abstract : OBJECTIVES: To investigate the relationship between oliguric acute kidney injury (AKI) and mortality in patients with acute respiratory distress syndrome (ARDS). DESIGN: Retrospective cohort study. SETTING: This investigation took place at a single-center, tertiary referral multidisciplinary comprehensive healthcare hospital in metropolitan Detroit, Michigan. PATIENTS: Adult patients 18 years old or older hospitalized in the ICU and diagnosed with ARDS on mechanical ventilation. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Three hundred eight patients were included in the final analysis. Risk factors associated with mortality included advanced age ( p < 0.001), increased body mass index ( p = 0.008), and a history of chronic kidney disease ( p = 0.023). Presence of AKI by day 1 of intubation, with elevated creatinine ( p = 0.003) and oliguria ( p < 0.001), was significantly associated with mortality. On multivariate analysis, advanced age (relative risk [RR], 1.02), urine output on the day of intubation (RR, 0.388), bicarbonate level (RR, 0.948), and Sequential Organ Failure Assessment severity score (RR, 1.09) were independently associated with mortality. A receiver operating characteristic curve identified a threshold urine output on the day of intubation of 0.7 mL/kg/hr (area under the curve, 0.75; p < 0.001) as most closely associated with inpatient mortality (i.e., urine output < 0.7 mL/kg/hr is associated with mortality). CONCLUSIONS: For patients with ARDS, oliguria on the day of intubation was independently associated with increased mortality. Urine output of less than 0.7 mL/kg/hr predicted 80% of inpatient deaths. These findings herald an augmented understanding of the role of urine output in medical decision-making and prognostication.